Bioptic diagnosis of adrenal gland tumours in patients with lung neoplasms - Chorąży, Marek; Wiąk, Zbigniew; Głasek, Jędrzej (Contemporary Oncology/Współczesna Onkologia, 2008)
Between January 2003 and June 2007 the authors performed 837 CT examinations of patients with histopathologically confirmed lung cancer. They were 627 males and 210 females. In 46 cases the CT image showed the suspicion of the presence of tuberous proliferation in adrenal glands. Only in 36 patients were we able to depict enlarged adrenal glands, and these patients had a guided biopsy done. 29 patients had the specimen taken from one adrenal gland, 7 patients from both. All tuberous lesions in both adrenal glands were benign. In 29 patients a single tumour of the adrenal gland turned out to be a neoplastic metastasis. It was found that: • lung cancers in 3.2% of cases give metastases to the adrenal glands, • these are metastases to one adrenal gland, • there is no relation between kind of tissue and metastasis frequency and adrenal gland tumours are most frequently located on the same side as the primary focus.